(untitled) (Nigerian Journal of Pharmaceutical Research, 2024)
Background and objectives: Various parts of Mimosa pigra (MPG) are used in traditional medicines to treat convulsive disorders. The objective of this study was to investigate the anticonvulsant properties of Mimosa pigra ethanol root extract (EREM). Methods: The acute toxicity of the extract was investigated using OECD 423 protocol of 2002. The anticonvulsant properties of EREM at 200,400 and 800 mg/kg were evaluated using Maximal Electroshock Test (MEST) in chicks; strychnine (SCN-) and pentylenetetrazole (PTZ)-induced seizures in mice. Results: The extract at 400 and 800 mg/kg significantly (p<0.05) prolonged the mean onset of clonic and tonic convulsions in mouse model of SCN-induced seizure. In PTZ-induced seizure, the extract at 400 mg/kg significantly (p<0.05) increased the mean onset of clonic seizure, while at 800 mg/kg, there was significant (p<0.05) prolongation in the mean onset of clonic and tonic seizure compared to control. The extract did not protect the chick against MEST but significantly (p < 0.05) reduced the mean recovery time at the of 200, 400 and 800 mg/kg. The extract offered 60 and 100% protection at 400 and 800 mg/kg respectively in SCN-induced seizure. Similarly, EREM offered 20 and 40% protection at 400 and 800 mg/kg respectively in PTZ-induced seizure. Diazepam (10 mg/kg), a reference drug significantly (p<0.05) prolonged the onset of clonic-tonic seizure and protected against SCN-, and PTZ-induced convulsion in mice. Conclusion: These findings indicated that EREM may possess anticonvulsant activity in SCN-, and PTZ-induced seizure in mice. Thus, lend scientific credence to the anticonvulsant claim of EREM in ethnomedicine.